IbM PELATIHAN DAN PENDAMPINGAN KADER POSYANDU LANSIA DI DUSUN MUDAL SARIHARJO NGAGLIK SLEMAN - Istri Utami; Agustin Endriyani (Universitas Muhammadiyah Semarang, 2017)
Efforts to reduce morbidity in the elderly are preventive and promotive efforts that excite the spirit of life for old age to keep them extra and remain useful for themselves, family and society. Medical examination with elderly patients on the disease. Many problems such as diabetes, blood pressure, cholesterol are routinelydetected during medical examinations. A medical examination with an elderly patient is the best time to advise on managing stress, quitting smoking and weight loss.Posyandu elderly is a strategic step in the development of quality human resources in order to help and help yourself. Methods performed on community service is by making posyandu elderly and training cadres in the management of posyandu elderly.The purpose of the training program and facilitation of elderly posyandu cadres is to provide knowledge and skills to the posyandu cadres so that the active cadres do motivate the community to attend the posyandu elderly event. The activities that have been done are the media that have been prepared (leaflat and material),conducting the training of cadres, accompanying cadres in motivation to the community, providing health equipment for implementing posyandu elderly.The target and outcome is the realization of healthy and prosperous elderly society, the establishment of elderly posyandu cadres are protected, safe health degree for the elderly, the implementation of posyandu elderly program regularly once a month and the implementation of counseling thoroughly related to the health of the elderly. Disengagement activities from this activity, health cadres continue to be motivated to the community to always participate in activities posyandu elderly.Keywords: cadres, elderly posyandu, elderly health